KONTRAK DALAM KITAB UNDANG â UNDANG HUKUM PERDATA DAN HUKUM ISLAM (Suatu Kajian dalam Perspektif Asas â Asas Hukum) - Hapsari, Dwi Ratna Indri (REPERTORIUM, 2014)
Abstractcommon law system adopted by Indonesia affect contract law in Indonesia as well as the principle - principle.Â The principle - the principle of contract law in Indonesia is regulated in the Civil Code codification. In addition,Â Islamic law also applies in Indonesia has a legal agreement with the principle - the principle of a separateÂ agreement. Based on the principle of freedom of contract are contained in the civil code as well as IslamicÂ law every person has the right to contract freely, but there are limits. The principle - the principle of agreementÂ in the civil code mupun in Islamic law has some similarities and differences. The parties to implement theÂ agreement should be agreed before the contract is to be carried understand the principle - the principle ofÂ the contract in order to avoid it - it is not desirable as long as the contract lasts.AbstrakSistem hukum common law yang dianut Indonesia mempengaruhi hukum perjanjian di Indonesia serta asasÂ â asasnya. Asas â asas hukum perjanjian di Indonesia diatur dalam kodifikasi KUHPerdata. Selain itu HukumÂ Islam juga berlaku di Indonesia memiliki hukum perjanjian dengan asas â asas perjanjian tersendiri. BerdasarÂ pada asas kebebasan berkontrak yang terdapat dalam KUHPerdata maupun Hukum Islam setiap orang berhakÂ melakukan kontrak dengan bebas namun ada batasannya. Asas â asas perjanjian dalam KUHPerdata mupunÂ dalam Hukum Islam memiliki beberapa kesamaan dan perbedaan. Para pihak dalam melaksanakan perjanjianÂ hendaknya sebelum sepakat atas kontrak yang hendak dilaksanakan memahami asas â asas dalam kontrakÂ tersebut agar tidak terjadi hal â hal yang tidak diinginkan selama kontrak berlangsung.